The Quality of Intrapartum Care Questionnaire Based on the WHO Recommendations - OROVOU, EIRINI; Eskitzis , Panagiotis; Lilo, Marsida; Ymeraj, Marinela; Antoniou, Evangelia (International Journal of Innovative Research in Medical Science, 2022)
Childbirth is a unique experience for a woman’s life and for this reason, it is necessary to ensure the right conditions to have a positive childbirth experience. Thus, the World Health Organization has developed recommendations aimed at promoting normal childbirth and better care of the mother and fetus without unnecessary interventions. This study presents a questionnaire that measures the quality of intrapartum care according to the WHO interventions. The questionnaire was constructed for the needs of a Greek survey for the evaluation of delivery rooms by midwifery students, according to their observations during their internship.